Brachial plexus injury after microwave-based treatment for axillary hyperhidrosis and osmidrosis. (3rd October 2017) - Chang, Chun-Kai; Chen, Chun-Yu; Hsu, Kuo-Feng; Chiu, Han-Ting; Chu, Tzi-Shiang; Liu, Hung-Hui; Goh, Meng-Xun; Chen, Shyi-gen
ABSTRACT: Axillary hyperhidrosis combined with osmidrosis is a common problem, especially in Asian communities, that patients find annoying. Even though several surgical techniques have been reported to treat hyperhidrosis/osmidrosis permanently, patients would prefer a non-surgical approach. A microwave-based device was invented during this decade, and it has proven to be a safe and efficient way to treat axillary hyperhidrosis/osmidrosis without major complications. Mild complications reported are vacuum-associated marks, oedema, tenderness and temporary altered skin sensation. We herein report a rare case of brachial plexus injury with sensory and motor dysfunction that occurred after microwave-based treatment. The patient did not fully recover after 6 months of rehabilitation. Our case suggests that a lower initial energy level should be used for thin patients with less fat tissue on the underarm areas, regardless of the patient's sex.